Secret seven fire works - "Blyton, Enid" (Hodder Children's: London, 2002)
An enduringly popular series, now with fun new covers! Jack's little sister Susie is very annoying and the Seven are furious when she forms a rival club. But is she bad enough to have stolen some money?
Keywords: Adventure stories